Fuzzy adaptive LS channel estimation for GO-MC-CDMA - WANG Yan1; LIU Hong-li1; ZHAN Jie1 (Tongxin xuebao)
The channel frequency response was constructed by choosing a certain number of the first estimate value which was handled by FFT interpolation.Therefore,the model mismatch error could be compensated effectively.In addition,the relationship between the mean-squared error（MSE） and the number of chosen first estimate value was analyzed by consid-ering the influence of the noise on LS Estimation method.Thus,the optimal criterion for obtaining the optimum number of first estimate value was explored with a fuzzy algorithm.The simulations demonstrate that the fuzzy adaptive LS channel es-timation performs is much better than the traditional LS Channel Estimation and that it is more robust with noise.